Living standards, poverty and inequality in the UK: 2015-2016 to 2020-2021 - James Browne; Andrew Hood (Institute for Fiscal Studies (IFS), 2016)
Official data on the distribution of household incomes in the UK are available only with a significant lag: the latest statistics are for 2013-14. In this report, we use modelling techniques to provide a more up-to-date picture and to assess how things are likely to evolve in the coming years. Essentially, we estimate the implications for household incomes of policy changes already implemented since 2013-14 or planned by 2020-21, and of labour market trends already recorded from other data sources since 2013-14 or forecasted by the OBR up to 2020-21 ...
Keywords: 330